Türkiye’de gelişme iktisadının evrimi - Tabak, Mustafa (My University, 2002)
Bu tezin amacı, Türkiye'de gelişme iktisadının evriminin dönemsel incelemesini yapmaktır. Dönemsel incelemenin çerçevesini çizen değişimlerin incelenmesinde kullanılan verilerin elde edilebileceği bir makale dökümü hazırlandı. Bu makale dökümünden elde edilen veriler, tablolara döküldü ve bir şekil oluşturuldu. Söz konusu tablolar ve şekle göre 1960-69 döneminden 1970-79 dönemine makale sayısı/ Türkiye'de gelişme iktisadına duyulan ilgi artmış, 1970-79 döneminden 1980-89 dönemine azalmış, 1980-89 döneminden 1990-99 dönemine azalmıştır. Makale sayısı en yüksek/ Türkiye'de gelişme iktisadında ön planda olan konulara 1960-69 dönemi için toplum(köy) kalkınması, 1970-79 dönemi için planlama, plan(genel), planlı gelişme vb., 1980-89 dönemi için iktisadi gelişme vb. stratejisi, 1990-99 dönemi için eğitim vb. konuları örnek olarak verilebilir. Türkiye'de gelişme iktisadındaki söz konusu değişimler uluslararası alanda gelişme iktisadına göre farklılık göstermektedir; örneğin Türkiye'de gelişme iktisadına duyulan ilginin en fazla olduğu dönem 1970-79 dönemiyken uluslararası alanda gelişme iktisadı için aynı dönem 1960-69 dönemidir. Türkiye'de gelişme iktisadının evrim süreci uluslararası alanda gelişme iktisadının evrim sürecine, Türkiye'de yaşanan gelişme sürecindeki farklılıklarla koşut değildir.

Aim of this thesis is making periodical examine of evolution of development economics in Turkey. An article document has been prepared for getting data which is using for examine of periodical research frame. Data that got from this article document spilled to tables and a figure was formed. According to tables and figure in question from period of 1960-69 to period of 1970-79 article number/ interest being to development economics in Turkey was increased, from period of 1970-79 to period of 1980-89 it was decreased, from period of 1980-89 to period of 1990-99 it was decreased. For period of 1960-69 community (village) development, for period of 1970-79 planning, plan (general), planned development etc., for period of 1980-89 economic development etc. strategy, for period of 1990-99 education etc. subjects can gave as example to subjects which article number's highest/ being in most important in development economics in Turkey. Changes in question in development economics in Turkey are showing difference according to development economics in international area; for example while period which interest being most to development economics in Turkey is period of 1970-79 same period in development economics in international area is period of 1960-69. Evolution of development economics in Turkey is not parallel to evolution of development economics in international area with difference in development procces that has been living in Turkey.
Keywords: Ekonomik Gelişim_Türkiye